2017
DOI: 10.21037/jtd.2017.02.31
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pulmonary mucormycosis: an emerging fungal infection in diabetes mellitus

Abstract: A 60-year-old diabetic female presented with fever and productive cough with hemoptysis for two months. There was no significant past medical or surgical history. Crackles were audible at right middle and lower part of chest. Rest of the physical examination was unremarkable.On laboratory investigations, total leucocyte count (TLC) was 13.1×10 9 /L with 73.6% neutrophil, potassium (K) was 5.5 mg/dL, creatinine was 1.1 mg/dL. Glycated hemoglobin (HbA1c) was 13.1%. Serial chest X-rays showed persistent homogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Recent reclassification has abolished the class zygomycetes, and hence, the term zygomycosis is inappropriate for use, although it may still be used to address mucormycosis [1]. Pulmonary mucormycosis is a devastating and life-threatening infection if not correctly diagnosed and treated [9]. The mononuclear and polymorphonuclear phagocytes of normal hosts kill Mucorales by generation of oxidative metabolites and the cationic defensins.…”
mentioning
confidence: 99%
“…Recent reclassification has abolished the class zygomycetes, and hence, the term zygomycosis is inappropriate for use, although it may still be used to address mucormycosis [1]. Pulmonary mucormycosis is a devastating and life-threatening infection if not correctly diagnosed and treated [9]. The mononuclear and polymorphonuclear phagocytes of normal hosts kill Mucorales by generation of oxidative metabolites and the cationic defensins.…”
mentioning
confidence: 99%
“…It seems that in diabetic individuals with mucormycosis, early diagnosis, early surgery and necrotic tissue removal, appropriate antifungal therapy, and control of risk factors such as diabetes are the main parameters for successful management of this infectious disease [19]. It appears that the mortality rate of individuals with pulmonary mucormycosis is about 76% [20], while researchers in a study found that a lower mortality rate occur in individuals with only bronchial involvement due to the limited extent of the disease to the bronchial area [21].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of this disease is difficult because these fungi are not properly stained by routine laboratory stains and does not grow easily in the culture medium. The reliable diagnostic method for this fungus is microscopic examination [20]. The average time for diagnosis from the onset of the disease is about 16.2 days [22].…”
Section: Discussionmentioning
confidence: 99%
“…"Halo sign", "reversed halo sign" may be correlated with massive hemoptysis [14]. Diabetic patients are more at a risk of developing the endo-bronchial disease [15]. Our patient presented with sign and symptoms that mimic tuberculosis, so he was diagnosed as a case of TB outside and was started with anti-tubercular drugs.…”
Section: Casementioning
confidence: 97%